Psychiatric mental health nursing - Videbeck, Sheila L. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2001)
Ideal for use in an abbreviated or integrated Psychiatric Nursing curriculum, this handy resource presents sound nusing theory, therapeutic modalities, and clinical applications for the major DSM-IV-TR (2000) disorders across the treatment continum--from the hospital to the home.
Unit I: Curent theories and practice -- Unit II: Building the nurse-client relationship -- Unit III: Current social and emotional concerns -- Unit IV: Nursing practice for psychiatric disorders
Includes index.
Keywords: PSYCHIATRIC NURSING